2017
DOI: 10.1007/s10151-017-1705-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the national bowel screening program in the Netherlands on detection and treatment of endoscopically unresectable benign polyps

Abstract: BackgroundIn January 2014, a national bowel cancer screening program started in the Netherlands. The program is being implemented in phases until 2019. Due to this program, an increase in patients referred for a colorectal resection for benign, but endoscopically unresectable polyps, is expected. So far, most resections are performed according to oncological principles despite no pre-operative histological diagnosis of malignancy. The aim of this study was to analyze the increase in referred patients during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…In the international literature, a wide range of categories are used for rectal cancer volume at hospital level. Van Gijn et al calculated median cut-off points from published rectal cancer hospital volume studies, leading to a definition of a high-volume hospital a performing more than 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) rectal cancer resections per year and low-volume hospitals performing 9 (6-14) [28]. This hampers interpretation of the available literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In the international literature, a wide range of categories are used for rectal cancer volume at hospital level. Van Gijn et al calculated median cut-off points from published rectal cancer hospital volume studies, leading to a definition of a high-volume hospital a performing more than 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) rectal cancer resections per year and low-volume hospitals performing 9 (6-14) [28]. This hampers interpretation of the available literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the incidence of CRC significantly decreased by 76-90% with endoscopic removal of colorectal adenomatous polyps (4). In recent years, there was implementation of national colorectal cancer screening program in many countries and increasing detection of premalignant or early malignant colorectal polyps was observed (5). Most of the polyps can be removed by conventional endoscopic procedures, including cold/hot biopsy, snare polypectomy or endoscopic mucosal resection (EMR).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is necessary rather than merely considered desirable in an era of increased detection of SPECC lesions as a consequence of colorectal cancer screening . It is also imperative that advances in diagnostic and therapeutic technology in endoscopy require integration with clinically effective and cost‐effective healthcare processes in order to achieve the optimal individualized patient outcomes.…”
Section: Suggested Pathway For Decision‐making and Management Of Specmentioning
confidence: 99%
“…We suggest that this systematic approach should be considered as the standard of care rather than attempting often inappropriate therapy at the time of detection of the lesion without specific assessment or discussion with the patient regarding the appropriateness of treatment in their individual context and alternative treatment options that may be available and appropriate in a wider regional context. This approach is necessary rather than merely considered desirable in an era of increased detection of SPECC lesions as a consequence of colorectal cancer screening [10]. It is also imperative that advances in diagnostic and therapeutic technology in endoscopy require integration with clinically effective and costeffective healthcare processes in order to achieve the optimal individualized patient outcomes.…”
Section: Suggested Pathway For Decision-making and Management Of Specmentioning
confidence: 99%